Quantitative analysis of predominant yeasts and volatile compounds in the process of pickled wax gourd. Issue 1 (2nd January 2016) - Wu, Zu-Fang; Sun, Li; Zhang, Xin; Shen, Xi-Quan; Weng, Pei-Fang
Abstract : Yeasts have been reported to be responsible for flavor compound formation in, and the quality of, pickled wax gourd. In this study, the diversity of yeasts and their predominant species in pickled wax gourd, as well as the capability to produce aroma compounds were detected by 5.8 S rDNA-ITS clone library combined with RT-PCR technology and GC–MS. It showed the predominant yeast species in the pickling processing were Issatchenkia orientalis, Pichia kudriavzevii and Candida xylopsoci, and clones numbers of each yeast species reached 10 7 copies mL –1 . A total of 66 volatile constituents were identified and quantified, and the major volatile compounds of pure culture with yeast were alcohols, which were the critical flavor composition of pickled wax gourd. Together, these results could provide information about the quality control of pickled wax gourd including the flavor composition and the growth of predominant microbial species.